Whose Tax Burden? Whose Tax Fairness? And Whose Tax Reform? - St. John, Christopher (Maine Policy Review, 1997)
Current efforts to reform Maine’s tax system represent no new business, according to Christopher "Kit" St. John. In this second article in this issue about tax reform, St. John suggests the need to re-examine reform principles in Maine and, more particularly, reassess conventional wisdom that professes a relationship between tax reform and economic competitiveness. He examines recent reform proposals and offers a path forward, one based on relieving tax burden while maintaining tax fairness, especially for low income citizens of Maine.